2003
DOI: 10.1046/j.0305-0270.2003.00986.x
|View full text |Cite
|
Sign up to set email alerts
|

How does the taxonomic status of allopatric populations influence species richness within African cichlid fish assemblages?

Abstract: Aim  Current estimates of species richness within rapidly evolving species flocks are often highly dependent on the species status of allopatric populations that differ in phenotypic traits. These traits may be unreliable indicators of biological species status and systematists may have inconsistently assigned species among lineages or locations on the basis of these traits, thus hampering comparative studies of regional species richness and speciation rates. Our aim was to develop a method of generating stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 37 publications
1
88
0
1
Order By: Relevance
“…While the timing of the evolutionary processes in East African cichlids is fairly well documented (see above), there are ongoing debates on the taxonomic status of many cichlid species, lineages, and even species flocks (see e.g., Snoeks et al 1994;Turner et al 2001;Genner et al 2004). The taxonomy of the Tanganyikan cichlids is relatively well established (Poll 1986), which is mostly due to the existence of morphological characteristics that distinguish the different tribes and species.…”
Section: Three Areas Of Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…While the timing of the evolutionary processes in East African cichlids is fairly well documented (see above), there are ongoing debates on the taxonomic status of many cichlid species, lineages, and even species flocks (see e.g., Snoeks et al 1994;Turner et al 2001;Genner et al 2004). The taxonomy of the Tanganyikan cichlids is relatively well established (Poll 1986), which is mostly due to the existence of morphological characteristics that distinguish the different tribes and species.…”
Section: Three Areas Of Uncertaintymentioning
confidence: 99%
“…Within these tribes, the more recent radiation and speciation processes seem to be as well related to trophic morphologies (see, e.g., Sturmbauer et al 2003), whereas colorational differences are found within arrays of closely related species, for instance of the Cyprichromini and the Tropheini. Unlike in Lake Malawi, however, in Lake Tanganyika the different colored morphs are usually not considered as separate species (Poll 1986;Snoeks et al 1994;Genner et al 2004).…”
Section: Allopatric Intralacustrine Speciationmentioning
confidence: 99%
“…An estimated 660-1,319 species of cichlid fishes have been recorded from Lakes Malawi, Tanganyika, and Victoria, most endemic to a single lake catchment (12). These species flocks are so rich that, collectively, they provide the best example of rapid adaptive radiation in vertebrates (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…A greater understanding of geographical and phylogenetic ancestry of cichlids is required to test whether functional genetic variation under divergent selection within lake radiations is present within riverine ancestors, and whether this variation has been shared among riverine cichlids through intraspecific gene flow and interspecific hybridization [9]. Lake Malawi contains a radiating flock of at least 450 haplochromine species [11]. Early phylogenetic reconstructions suggested that the lake radiation was monophyletic [12,13].…”
Section: Introductionmentioning
confidence: 99%